USE OF INTERACTIVE METHODS IN TEACHING ENGLISH FOR TOURISM PURPOSES (Scientific journal of the Fergana State University, 2024)
This article aims to provide an overview of interactive methods of teaching English to students in the field of tourism, which has been developing significantly in recent times. The article is divided into two parts: the first part presents the importance of the English language in this field and the specific features of teaching a foreign language oriented to the profession; and in the second part, modern interactive methods used by teachers during foreign language lessons and to increase students' motivation to learn a language are interpreted. The experience of English language teachers of non-philological higher educational institutions shows that the organization of speech interaction in the lesson using traditional work methods and forms is not always effective. Today, the use of interactive methods and methods of teaching foreign language specialists of all fields shows its relevance. Practice shows that the use of interactive methods and methods in foreign language classes relieves the nervous tension of language learners, learns forms of activity allows to change, to focus on the main issues of the topic of employment. After all, the quality of the material supply and the efficiency of its acquisition will increase significantly, and as a result, the motivation of students to learn a foreign language will increase.